2024
DOI: 10.3390/gels10010068
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-Transformable Antioxidant Poly-γ-Glutamic Acid/Polyethyleneimine Hemostatic Powder for Efficient Wound Hemostasis

Xiang Li,
Wenli Han,
Gao He
et al.

Abstract: Hemostatic powder, which can absorb large amounts of water and tends to produce repeated hydration with tissue, has been clinically proven as an ideal engineering material for treating wounds and tissues. We herein designed a polypeptide-based hemostatic powder. A water-soluble polypeptide, γ-polyglutamic acid (γ-PGA), was mixed with the polyethyleneimine (PEI), N-hydroxysuccinimide, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. The solution of these polymers was lyophilized to harvest the γ-PGA/PEI powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that extensive inflammatory infiltration represents a common feature of chronic wounds, which hinders the repair of the wound in a chronological and biological sequence [ 199 ]. In parallel, rapid and effective hemostasis is of paramount importance to improve the wound healing process [ 200 ]. As a consequence, it may be necessary to incorporate additional agents alongside antioxidants within the hydrogel structure to effectively inhibit inflammation, promote hemostasis, and promote wound healing [ 201 , 202 ].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…It is worth mentioning that extensive inflammatory infiltration represents a common feature of chronic wounds, which hinders the repair of the wound in a chronological and biological sequence [ 199 ]. In parallel, rapid and effective hemostasis is of paramount importance to improve the wound healing process [ 200 ]. As a consequence, it may be necessary to incorporate additional agents alongside antioxidants within the hydrogel structure to effectively inhibit inflammation, promote hemostasis, and promote wound healing [ 201 , 202 ].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Polyvinyl alcohol (PVA) is a commonly used polymer for hydrogel fabrication because of its distinguished properties and excellent biocompatibility. In addition, PVA has been diversely applied to biomedical applications, such as hemostasis bandages, self-healing materials, 3D tissue scaffolds, and wound healing [ 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PTIO • has also attracted much attention as a redox mediator for batteries [35][36][37]. Recently, it has been reported that PTIO • can be used to estimate the activity of antioxidants as a reactivity model of reactive oxygen species [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. However, there is no report on the reactivity of PTIO • in the presence of redox-inactive metal ions.…”
Section: Introductionmentioning
confidence: 99%